The Relationship between the Painter’s Inner Energy and His Creativity in Canvas Painting - Homayounifar, Maryam; Amin Khandaqi, Javad (International Journal of Psychosocial Rehabilitation, 2020)
In this study, we examined the relationship between the painter’s inner energy and his creativity in the canvas. For this study, a sample of 100 art students was selected by convenience sampling. The design of this study was descriptive-surveying and the statistical method was a correlation. Tools were used to measure research variables, one to measure the painter’s intrinsic motivation and energy and the other to measure his creativity in the phenomenon of a canvas on a painting canvas. The results of the data extracted from the research tools after entering the SPSS software showed that the painter’s internal motivation and energy had a positive, direct and significant relationship with his creativity. Both of these variables were associated with a decrease in the other variable.